Pengaruh Instagram Terhadap Gaya Hidup Mahasiswa Fakultas Ilmu Komunikasi Universitas Islam Nusantara - Fitri Khoiriyyah Nissa; Fitri Sukayawati; Muhammad Willy Indriana (Kampret Journal, 2022)
This study aims to reveal how the lifestyle of the students of the Faculty of Communication Sciences, Universitas Islam Nusantara after carrying out activities on Instagram social media. This study uses a descriptive approach with quantitative research methods. This method provides an overview of how the influence of Instagram social media on the lifestyle of the students of the Faculty of Communication Sciences, Universitas Islam Nusantara. The quantitative descriptive research method instrument that the researcher uses is a questionnaire (questionnaire). This study seeks information about the impact of Instagram on student behavior, as well as how respondents respond to Instagram which is currently booming.